Sequence control of a reactor system by using programmable logic controller / Nik Azahar Nik Yahya and Mohd Noor Ismail - Nik Yahya, Nik Azahar; Ismail, Mohd Noor (1988)
This project is about the application of Programmable Logic Controller (PLC) in controlling the sequence of a reactor system. In order to design a good control system, a study of the characteristic of the PLC and the equipments used will be required. In this project, the PLC is used to control water flow, level and temperature. This is very important in—industry since the flow, level and temperature are directly related to the process sequence.